Innate immune sensing and vaccine strategies against West Nile virus: role of Toll-like receptors and viral evasion mechanisms - Kayesh, Mohammad Enamul Hoque; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Microbiology, 2025)
The West Nile virus (WNV), an emerging neurotropic flavivirus and a leading cause of viral encephalitis worldwide, represents a significant public health threat owing to its neuroinvasive potential and the absence of a licensed human vaccine. Understanding the host immune response to WNV, particularly the role of Toll-like receptors (TLRs), is critical for elucidating viral pathogenesis and developing therapeutic strategies. TLRs are essential for the detection of viral components, initiation of innate immunity, and shaping of adaptive responses. Despite progress in research, no clinically approved WNV vaccine is currently available for humans, highlighting the urgent need for effective vaccine development. This review summarizes the current knowledge regarding the TLR-mediated immunity in WNV infection, with a focus on immune activation mechanisms and viral evasion strategies. Furthermore, we examine recent advances in vaccine development, emphasizing the potential of TLR agonists as adjuvants to enhance immunogenicity and protective efficacy.